The Application of Indonesian Environmental Administrative Law with Regard to Criminal Considerations - Tuti Handayani; Rukmono, Indra; Lie Epifani R. Gunadi; Elmi Sasmitaningtyas; Abd. Rohman (Universitas Kristen Cipta Wacana, 2024)
In addition to examining the evolution of democracy under the rule of law from the standpoint of environmental law enforcement in Indonesia, the purpose of this study is to identify the elements of environmental management law enforcement in Indonesia and the administrative penalties associated with environmental law enforcement. The research methodology in this study takes a legal perspective. Descriptive-analytic research methodology is employed. Since Indonesia is a state of law, including environmental law enforcement, descriptive analysis with a qualitative approach was employed as the data analysis method in this study. Administrative penalties are one way that environmental laws are enforced. Legal penalties known as administrative sanctions are those that authorities of the government can apply without first bringing charges against people or organizations that break environmental administrative legislation. The primary purpose of administrative sanctions is to serve as a tool for controlling illegal activity. According to the organic state theory, the state has controlled the application of administrative sanctions in order to control every action and/or enterprise in the environmental sector, as seen from the standpoint of environmental management legislation enforcement in Indonesia. Prevent negative effects on the environment, such as pollution and/or environmental harm. Legal penalties known as administrative sanctions are those that authorities of the government can apply without first bringing charges against people or organizations that break environmental administrative legislation. The primary purpose of administrative sanctions is to serve as a tool for controlling illegal activity. According to the organic state theory, the state has controlled the application of administrative sanctions in order to control every action and/or enterprise in the environmental sector, as seen from the standpoint of environmental management legislation enforcement in Indonesia. Prevent negative effects on the environment, such as pollution and/or environmental harm.